Microbial production of food grade pigments – screening and metabolic pathway analysis - Kamarudin, Kamarul Rahim (2009)
Unitl recently, the use of plant pigments as natural food colourantis expensive and uncompetitive to synthetic dyes due to their high production costs. Such disadvantages could be overcome with the development of microbial food grade pigments which are likely to cut down the high production cost, thus leading to a cheaper source of natural food colournats. The production of natural colourantsby microbial fermentation has a number of advantages over plant-based systems such as higher yeilds within a shorter period of time and no seasonal varations. We, therefore, have screened 285 microbial strains from our NewZealand environmental microorganism collection to find new sources of natural food grade pigments. Among those, 166 strains produced pigments when growing in liquid medium including 28 extracellular pigments and 90 intacellular pigments. HLPC results showed that 33 purified pigments were water soluble. Molecular indentification of 39 selected strains using ribosomal DNA sequencing showed the presence of representativrs from 19 different genera. Interestingly, a number of pigments have shown biological activity against filamentous fungi. We currently carrying out pigment stability tests on selected microbial strains. Futher to this study, metabolomics and metabolic engineering tools will be used for improvement of pigment yield of the best candidate strain with potential for industiral applications.